Study of the influence of the rare earth elements (Ce3+ and Ce4+) concentration on the siloxanes coating applied on the copper surface - Basho, É N.; Sakai, R. T.; Da Cruz, F. M D L [UNESP]; De Melo, H. G.; Benedetti, Assis Vicente [UNESP]; Suegama, P. H. (The Electrochemical Society, 2012)
This work studied the influence of the rare earth (Ce3+ and Ce4+) elements concentration in polysiloxane flints deposited on copper by dip-coating process, and evaluated their resistance in a 3.5 wt.% NaCl medium. Classical electrochemistry techniques were used as open circuit potential, polarization curves and electrochemical impedance spectroscopy. The results revealed that by adding low concentration of Ce4+ ions, the coating prevents the electrolyte uptake any longer retarding the substrate degradation consequently. ©The Electrochemical Society.
Keywords: Copper surface; Dip-coating process; Low concentrations; Open circuit potential; Polarization curves; Substrate degradation; Copper; Degradation; Electrochemical impedance spectroscopy; Electrochemistry; Silicon compounds; Silicones; Coatings